Kinerja Penyuluh Pertanian dalam Memanfaatkan Alat Digital pada Era New Normal di Provinsi Lampung bagian Utara - Gitosaputro, Sumaryo; Yanfika, Helvi; Nurmadani, Nurmadani; Nurhaliza, Siti; Irawan, Sahrul Ari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to determine the factors related to the performance of AEWs and the obstacles faced by agricultural extension workers, as well as to understand the relationship and impact of digital implementation in the New Normal era on supporting the performance of agricultural extension workers in Northern Lampung Province. The research was conducted from May 2022 to June 2022 in Northern Lampung Province. The respondents included 5 agricultural extension workers (AEWs) and 45 rice farmers. The research employed a descriptive quantitative method and Spearman rank correlation test. The results show that the factors related to the performance of agricultural extension workers in the northern part of Lampung Province include the age of the extension workers, level of formal education, work experience, level of work motivation, number of family members, distance from home to the workplace, availability of facilities and infrastructure, as well as the extension methods used. Agricultural extension workers face several challenges, such as limited funding, low farmer participation and attendance, inadequate facilities, and communication barriers. Digital technologies such as cyber extension and smart farming greatly support the improvement of their performance. In Northern Lampung, namely North Lampung and Tulang Bawang Barat, digitalization has also contributed to strengthening the role of extension workers in enhancing food security and improving farmer welfare.